The Skull Vibration-Induced Nystagmus Test of Vestibular Function—A Review - Dumas, Georges; Curthoys, Ian S.; Lion, Alexis; Perrin, Philippe; Schmerber, Sébastien (Frontiers in Neurology, 2017)
A 100 Hz bone conducted vibration (BCV) applied to either mastoid induces instantaneously a predominantly horizontal nystagmus, with quick phases beating away from the affected side in patients with a unilateral vestibular loss (UVL). The same stimulus in healthy asymptomatic subjects has little or no effect. This is skull vibration induced nystagmus (SVIN) and it is a useful, simple, non-invasive, robust indicator of asymmetry of vestibular function and the side of the vestibular loss. The nystagmus is precisely stimulus-locked: it starts with stimulation onset and stops at stimulation offset, with no post-stimulation reversal. It is sustained during long stimulus durations; it is reproducible; it beats in the same direction irrespective of which mastoid is stimulated; it shows little or no habituation; it is permanent – even well compensated UVL patients show SVIN. A SVIN is observed under Frenzel-goggles or videonystagmoscopy and recorded under videonystagmography in absence of visual-fixation and strong sedative drugs. Stimulus frequency, location, and intensity modify the results and a large variability in skull morphology between people can modify the stimulus. SVIN to 100 Hz mastoid stimulation is a robust response. We describe the optimum method of stimulation on the basis of the literature data and testing more than 18,500 patients. Recent neural evidence clarifies which vestibular receptors are stimulated, how they cause the nystagmus, why the same vibration in patients with semicircular canal dehiscence (SCD) cause a nystagmus beating towards the affected ear. This review focuses on the optimal parameters of the stimulus and response of UVL and SCD patients, but also shows how other vestibular dysfunctions affect SVIN. We conclude that the presence of SVIN is a useful indicator of the symmetry of vestibular function between the two ears, but in order to identify which is the affected ear, other information and careful clinical judgement is needed.